PENERAPAN MODEL PEMBELAJARAN READING ALOUD BERBANTUAN BUKU CERITA PEMBENTUK KARAKTER BAIK DI KELAS IV SD NEGERI 2 KAYUAGUNG - Revalina; Muhamad Idris; Nugroho Notosutanto Arhon Dhony (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is based on the low level of reading comprehension skills and the less-than-optimal development of students' character in elementary schools due to learning methods that are still monotonous and teacher-centered. The purpose of this study is to describe the implementation of the reading aloud learning model supported by character-building storybooks, both in improving engagement, reading comprehension, and students' character values. The method used is descriptive qualitative with research subjects consisting of fourth-grade students and a teacher at SD Negeri 2 Kayuagung. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used data reduction, data presentation, and conclusion drawing with validity testing through source triangulation. The results of the study show that the implementation of reading aloud can increase students' active engagement, help comprehension of reading content, and foster character values such as honesty, responsibility, and social awareness. In addition, the use of interesting storybooks containing moral values strengthens the process of character internalization in students. Thus, the reading aloud learning model supported by storybooks has proven to be effective as an alternative in literacy learning and character education in elementary schools.